Pengaruh Perendaman Kawat Nikel-Titanium Termal Ortodonti dalam Minuman Teh Kemasan terhadap Gaya Defleksi Kawat (The Effect of Immersion Thermal Nickel-Titanium Archwire in The Bottled Tea Drinks to The Archwire Force Deflection) - Halimatus Sa'diyah Hasyim; Leliana Sandra Devi AP; Agus Sumono (Pustaka Kesehatan, 2017)
Background: The acidic salivary pH cause potentially undergo orthodontic wire constituentmetal ions release. The release of metal ions can affect the quality of orthodontic wire.Objective: To analyze the effect of immersion thermal NiTi archwire in the bottled tea drinks tothe archwire force deflection. Material and Methods: The sample size were 12 round thermalNiTi orthodontic archwires (3M; 0,016 inch) which divided into three groups: a control group(artificial saliva), a group of bottled tea drinks and bottled tea drinks of fruit flavors. The sampleswere immersed in an incubator for 10.5 hours at 37 ° C. The deflection test used Three-PointBending method with a Universal Testing Machine in each group. Results and Conclusion:The results of One Way ANOVA test obtained value of 0.768 (p>0.05) which indicates that nosignificant difference in each group. The conclusion from this study is the bottled tea drinks cannot affect the force deflection of thermal NiTi orthodontic archwires.Keywords: Bottled tea drinks, Force deflection, NiTi thermal archwire